End‐stage renal disease treatment options education: What matters most to patients and families. Issue 2 (7th January 2018) - St. Clair Russell, Jennifer; Boulware, L. Ebony
Abstract: Treatment modality education can offer many important benefits to patients and their families. Evidence suggests such education can increase use of home dialysis, reduce catheter use, decrease 90‐day mortality, and increase transplantation. While these benefits are encouraging, not all patients are offered options education and when they are, it may not be presented in a way that is immediately applicable to them and their lives. Furthermore, little is known regarding specific characteristics (e.g. format such as group or individual or in‐person or online, duration, teaching methods, location, content) of educational programs that are most successful. No single approach has emerged as a best practice. In the absence of such evidence, adult learning principles, such as involving patients and families in the development programs and materials, can serve as a guide for educational development. Adult learning principles can enhance options education, evolving them from information delivery to a person‐centered, values‐based endeavor that helps match treatment to values and lifestyle.